Spaces of Intemperance & the British Raj 1860–1920. Issue 4 (3rd July 2020) - Goodman, Sam
ABSTRACT: The history of the British Empire in India is one awash with alcohol. Drinking was a common practice throughout colonial society, acting as social necessity and source of a public anxiety. However, rather than only acknowledging what and why individuals in colonial India drank, it is of equal importance to consider where they did so. Despite its ubiquity, alcohol consumption in India was responsive to the dynamics of space and place, and both the habits of drinkers and the social, military or governmental response to their actions altered greatly depending on locations individuals were able to access, and in which they consumed alcohol. This article draws focus on the spatiality of colonial drinking through an examination of key environs that characterise the British experience of India, and in which colonial Britons drank regularly. Examining published sources alongside archival material, the article argues that drinking in colonial India is rendered simultaneously private and public, personal and socially performative, as a result of the hybrid spaces in which individuals access alcohol. The culture of drinking in colonial context, and the manner through which the drinker is constantly under scrutiny makes the act of drinking as much to do with social performance as it is to do with personal taste, with space in each instance a governing influence on choice of beverage, intent, behaviour, and the perceived identity of the drinker themselves.